Mechanismbased role of the intestinal microbiota in gestational diabetes mellitus: A systematic review and meta-analysis - Yan, Min; Guo, Xiaoying; Ji, Guiyuan; Huang, Rui; Huang, Dongyi; Li, Zhifeng; Zhang, Dantao; Chen, Siyi; Cao, Rong; Yang, Xingfen; Wu, Wei (Frontiers in Immunology, 2023)
Background:Metabolic disorders caused by intestinal microbial dysregulation are considered to be vital factors causing Gestational Diabetes Mellitus (GDM). Increasing evidence suggests that the diversity and composition of gut microbes are altered in disease states, yet the critical microbes and mechanisms of disease regulation remain unidentified. Methods:PubMed, Embase, Web of Science and Cochrane databases from 7th July, 2012 to 7th July, 2022 were searched for case-control and controlled studies comparing the differences in enterobacteria between GDM and healthy individuals and the relative abundance of enterobacteria was collected for comparative diversity comparison, and enterobacterial differences were analyzed using random effects to calculate standardized mean differences at 5% p value. Result:The results showed a total of 22 studies were included in this review, and a total of 965 GDM and 1508 controls were collected. Alpha diversity did not differ between the participant groups, while where beta diversity was significantly different. Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria were the dominant bacteria, but there was no significant difference between the two groups. Qualitative analysis showed that Firmicutes / Bacteroidetes, Blautia and Collinsella developed a significant trend in the group. The results, however, were not statistically different. Conclusion:Enterobacterial profiles were significantly different between GDM and NGDM populations. Compared with healthy people, GDM people shares a stable alpha diversity, but the beta diversity is significantly different. Firmicutes / Bacteroidetes values were significantly increased in GDM, as well as changes in Blautia and Collinsella may be responsible for changes in microbiota diversity. Although the result of our meta-analysis is encouraging, more well-conducted studies are needed to clarify the role of gut microbiome in GDM.